2015
DOI: 10.1128/jvi.03634-14
|View full text |Cite
|
Sign up to set email alerts
|

Viral Semaphorin Inhibits Dendritic Cell Phagocytosis and Migration but Is Not Essential for Gammaherpesvirus-Induced Lymphoproliferation in Malignant Catarrhal Fever

Abstract: Viral semaphorins are semaphorin 7A (sema7A) mimics found in pox-and herpesviruses. Among herpesviruses, semaphorins are encoded by gammaherpesviruses of the Macavirus genus only. Alcelaphine herpesvirus 1 (AlHV-1) is a macavirus that persistently infects wildebeest asymptomatically but induces malignant catarrhal fever (MCF) when transmitted to several species of susceptible ruminants and the rabbit model. MCF is caused by the activation/proliferation of latently infected T lymphocytes. Viral semaphorins have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Bovine turbinate fibroblasts (BT, ATCC CRL-1390) and MacT-Cre cells2634 were cultured in Dulbecco’s modified essential medium (D-MEM, Invitrogen Corporation). Madin-Darby bovine kidney cells (MDBK, ATCC CCL-22) were cultured in modified essential medium (MEM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine turbinate fibroblasts (BT, ATCC CRL-1390) and MacT-Cre cells2634 were cultured in Dulbecco’s modified essential medium (D-MEM, Invitrogen Corporation). Madin-Darby bovine kidney cells (MDBK, ATCC CCL-22) were cultured in modified essential medium (MEM).…”
Section: Methodsmentioning
confidence: 99%
“…The entire genome of strain C500 has been cloned from low-passage, virulent virus as a bacterial artificial chromosome (BAC), in which infectivity and pathogenicity have been shown to be preserved24. The BAC clone is therefore an invaluable tool for studying the biology and pathogenesis of MCF78252627. The overall genome of strain C500 has been shown to be present in the BAC clone24, but the full sequence, and therefore the possible existence of undetected genetic changes, has not been determined.…”
mentioning
confidence: 99%
“…5B). Together, these data suggested that the TeHV-3 TE7 protein might also signal through Plexin-C1 and function similarly to other viral SEMAs (56). As for the TE8 protein, its sequence exhibits most of the residues found in the two family signature motifs characteristic of all cellular IL-10s:…”
Section: Resultsmentioning
confidence: 96%
“…The finding that the TeHV-3 TE7 and TE8 genes encode SEMA and IL-10 homologs, respectively, is particularly interesting for the following reasons. First, SEMA homologs have been reported in the family Herpesviridae only in the Macavirus genus of subfamily Gammaherpesvirinae (56). Second, although numerous IL-10 homologs have been described in the subfamilies Betaherpesvirinae and Gammaherpesvirinae (42), they have not been reported in the subfamily Alphaherpesvirinae.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the secreted viral semaphorins from pox and herpes viruses, which harbor some degree of homology to Sema7A, were demonstrated to affect DC adhesion, migration, and phagocytosis by acting on the cytoskeleton through plexin C1 (34,35).…”
Section: Discussionmentioning
confidence: 99%